The Neurosciences and Music II From Perception to Performance - Avanzini, Giuliano; Lopez, Luisa; Koelsch, Stefan; Majno, Marie (New York, NY New York Academy of Sciences, 2005)
The intricate relationships between music and human neurological makeup, as well as the ways in which music can influence neurological development, are explored in this volume, which is a continuation and expansion of two symposia that have preceded it, both of which have been published as Annals volumes. Researchers in the fields of neurophysiology, neuroimaging, mind-brain studies, and psychology present findings on the evaluation of neurological disorders and music, the relationship of music to development and language, and musical perception. The use and impact of music therapy is discussed in a roundtable format. Do animals have music? How is music similar to language? How is music represented mentally? This volume addresses these questions and others surrounding this exciting and growing field?a field that generates interest far beyond the boundaries of the neuroscientific world, encompassing education, performance, and the appreciation of music by all peoples. The book also offers articles written from the perspective of the fields of ethology and evolution, as well as papers on vocal learning, auditory perception, performance, and emotional response to music.
Keywords: Music psychology; Science; Emotion; Linguistics